Total chlorophyll and nutrients content in bean plants and weeds in competition - Ribeiro, Victor Hugo Vidal; da Silveira Júnior, Marcos Antônio; Pereira, Gustavo Antônio Mendes; Ferreira, Evander Alves; Silva, Enilson de Barros; dos Santos, José Barbosa (Comunicata Scientiae, 2018)
Plants compete for several resources on soil, including water, light and nutrients which can affect crop yield and also weeds growth. Under the hypothesis that in different densities and weed communities, crops and weeds undergo changes in their nutritional contents of macro and micronutrients, the aim of this study was to quantify the nutritional contents of bean plants and weeds cultivated in increasing densities (0, 74, 147, 221 and 295 plants m-2) and the effect of the association of plants (isolated bean, bean + Urochloa plantaginea, bean + Bidens pilosa and bean + Urochloa plantaginea + Bidens pilosa). The contents of macro and micronutrients were evaluated. The increase in plant density promoted a decrease in the total chlorophyll content of bean plants and weeds, as well as a decrease in macronutrients (K and P) and micronutrients (Zn, Fe, Mn and Cu). In the arrangement where the greatest number of species were cultivated simultaneously and in increasing densities, a greater reduction in total chlorophyll content and in macro and micronutrient contents of the three species (crops and weeds) were observed.